Развитие теории государственного управления: исторические этапы становления и совершенствования государственного менеджмента, организационно-экономического механизма и инструментария его осуществления (Путеводитель предпринимателя)
The article examines the main theoretical concepts of management tools to improve governance in the context of administrative reform, the transformation of public administration and local self-government in the provision of public services.